Program Fisioterapi Pada Kasus Osteoarthritis Knee Dextra:Case Report - Aisyah Nurul Khasanah; Farid Rahman; Anas Pradana (Jurnal Kesehatan dan Fisioterapi, 2022)
Introduction: Knee Osteoarthritis is degenerative joint disease due to chronic inflammation of knee joint which is characterized by progressive cartilage damage, osteophyte formation, and change in synovial membrane. In Indonesia, prevalence of Knee Osteoarthritis < 40 years old is 5%, 40-60 years old is 30%, and > 61 years old is 65%. Some complaints experienced by patients with Knee Osteoarthritis include pain, musle weakness, decreased stability of knee joint, brief morning stiffness, a “crack” sound in knee when it’s bent or straightened, and decreased functional ability. Objective: to determine the effect of giving Ultrasound (US), Transcutaneous Electrical Nerve Stimulation (TENS), Quadriceps Strengthening, and Hamstring Stretching in patients with Knee Osteoarthritis. Methods: this study used case report method which was carried out at PKU Muhammadiyah Bantul in Ny. T 69 years old on February 2022 with 3 times of therapy. Result: after 3 times of therapy, there was decrease in pain, increase in range of motion, increase in muscle strength, and increase in functional ability. Conclusion: giving US, TENS, Quadriceps Strengthening, and Hamstring Stretching are proven to be able to reduce pain, increase range of motion, muscle strength, and functional ability in patients with Knee Osteoarthritis.Keywords: Osteoarthritis Knee, Ultrasound (US), Transcutaneous Electrical Nerve Stimulation (TENS), Quadriceps Strengthening, Hamstring Stretching